2012
DOI: 10.1093/jjco/hys129
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Management of an Implanted Intraperitoneal Access Port System for Intraperitoneal Chemotherapy for Gastric Cancer with Peritoneal Metastasis

Abstract: Intraperitoneal chemotherapy for gastric cancer using a port is safe and feasible under appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 17 publications
2
24
0
9
Order By: Relevance
“…Complications associated with the port system occurred in 20.6% of 131 patients at our institution [40] . Inflow obstruction and infection were the main complications that occurred in 7.6% and 6.9% of patients, respectively.…”
Section: Peritoneal Access Port Systemmentioning
confidence: 80%
“…Complications associated with the port system occurred in 20.6% of 131 patients at our institution [40] . Inflow obstruction and infection were the main complications that occurred in 7.6% and 6.9% of patients, respectively.…”
Section: Peritoneal Access Port Systemmentioning
confidence: 80%
“…Emoto et al reported that complications associated with the port system occurred in 20.6% of 131 patients in their study [24]. Inflow obstruction and infection were the main complications that occurred in 7.6 and 6.9% of the patients, respectively.…”
Section: Rationale and Methodology For Intraperitoneal Chemotherapymentioning
confidence: 87%
“…Schaeff et al reported six cases of PSM from gastric cancer, where five of the six patients underwent diagnostic laparoscopy with liver metastasis or peritoneal dissemination [14]. Our group previously reported that subcutaneous port-site metastasis was observed in 2 (1.5 %) of 131 patients who had peritoneal metastasis of gastric cancer and received intraperitoneal chemotherapy through an implanted subcutaneous infusion port [17]. PSM after laparoscopic gastrectomy has rarely been reported since the first case in 2007 [18].…”
Section: Psm After Laparoscopic Surgery For Gastric Cancermentioning
confidence: 93%